Frank Joseph Shulman (comp. & ed.), Doctoral Dissertations on Japan and on Korea, 1969-1979: An Annotated Bibliography of Studies in Western Languages, Seattle and London, University of Washington Press, 1982, XV + 473 pp. - Quartucci, Guillermo (El Colegio de México, 1984)
-